2019
DOI: 10.1002/adom.201901512
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal Red Phosphors: Enhanced Optical Efficiency and Improved Chemical Stability for wLEDs

Abstract: Crystal phosphors have many unique advantages compared with powdery ones. Herein, room‐temperature‐grown millimeter‐sized single‐crystal phosphors of Cs2XF6:Mn4+ (X = Ge, Si, and Ti) with remarkably higher external quantum efficiency than the corresponding powdery samples are reported. In addition, as compared with the powdery ones, the crystal samples exhibit much better stability toward water under different pH conditions. The red light‐emitting diodes (LEDs) based on Cs2XF6:Mn4+ crystals show significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 28 publications
(4 reference statements)
0
37
0
Order By: Relevance
“…Stable and efficient white‐light emission is necessary for lighting applications. Currently, the most used solid‐state lighting sources are the phosphor‐converted LEDs based on blue‐emitting chip, a class of mixed and multiple emitters 90,91 . Although this type of light source has the advantages of high efficiency and high brightness, its shortcomings are also obvious, such as the efficiency losses caused by self‐absorption, the instability of colors due to the different degradation rates of phosphors, the complex device structure and the use of rare earth elements, and so forth 92 .…”
Section: Photoelectric Applications Of Halide Perovskitesmentioning
confidence: 99%
“…Stable and efficient white‐light emission is necessary for lighting applications. Currently, the most used solid‐state lighting sources are the phosphor‐converted LEDs based on blue‐emitting chip, a class of mixed and multiple emitters 90,91 . Although this type of light source has the advantages of high efficiency and high brightness, its shortcomings are also obvious, such as the efficiency losses caused by self‐absorption, the instability of colors due to the different degradation rates of phosphors, the complex device structure and the use of rare earth elements, and so forth 92 .…”
Section: Photoelectric Applications Of Halide Perovskitesmentioning
confidence: 99%
“…It is known that single crystals usually have more advantages over TC and PIG, and could be a good choice to increase transparency, improve efficiency, and maintain high waterproofness. Therefore, the performance of WLEDs packaged with crystals will certainly be enhanced, including energy conversion efficiency, stability, and lifetime [19] . There are many mature methods to grow high‐quality YAG:Ce 3+ single crystal [2] .…”
Section: Figurementioning
confidence: 99%
“…[27] As shown in Figure S12a-c (Supporting Information), the EQE of KSFM (3d) crystal is as high as 78.2%, which is much higher than that of the KSFM-CP phosphor (67.5%). Moreover, the EQE of KSFM (3d) is higher than those of the previously reported Mn 4+ -doped fluoride phosphors, such as K 2 GeF 6 :Mn 4+ (73%), [10] K 3 AlF 6 :Mn 4+ (51%), [4d] Rb 2 GeF 6 :Mn 4+ (58%), [28] Cs 2 SiF 6 :Mn 4+ (71%), [8] K 2 TiF 6 :Mn 4+ (60.0%), [7a] and Cs 2 GeF 6 :Mn 4+ (66.9%) single crystals, [29] suggesting great potential during the commercial applications. It is also noted that the internal quantum efficiency (IQE) of the KSFM (3d) (90.4%) is lower than the commercial KSFM-CP (93.3%) due to the increasing of direct energy transfer to quenching sites (defects and impurity ions).…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] A possible way is originated from the elemental impurities (OH − , O 2− , Mn 3+ , Mn 2+ ) defects causing quenching either by energy transfer or metalmetal charge transfer in typical K 2 SiF 6 :Mn 4+ phosphors, [32] and more backscattering and self-absorption of the KSFM-CP phosphor particles increase the nonradiative loss. [29] The photoluminescence decay curves at various temperatures are shown in Figure S13c,d (Supporting Information), and the temperature dependence lifetime can be seen in Figure 4d. It is found that the KSFM(3d) and the KSFM-CP basically have the same decay trend with elevated temperatures, indicating that the increase of doping concentration will not significantly affect the luminescence attenuation of Mn 4+ even at high temperature.…”
Section: Introductionmentioning
confidence: 99%